Antidiabetic and antihyperlipidemic effects of alcoholic and aqueous stem bark extracts of Limonia acidissima, linn in alloxan induced diabetic rats - Bhupendra Kumar Kumawat,; Tara Chand,; Yogendra Singh, (International Journal of Phytomedicine, 2012)
The present study was designed to investigate the antidiabetic and antihyperlipidemic effects of the alcoholic and aqueous extract obtained from the stem bark of Limonia acidissimaLinn (Rutaceae) using alloxan induced diabetic model in rats for 14 days. The alcoholic extract (200mg/kg) showed significant activity (P<0.01) in lowering blood glucose level than the aqueous extract (200mg/kg) which was comparable to glibenclamide (5mg/kg), a standard antidiabetic drug. Different biochemical parameters i.e. TGL(triglycerides), HDL, LDL, VLDL and total cholesterol level were also carried out which show that both alcoholic and aqueous extracts has significantly (p<0.001) reversed the diabetes-included hyperlipidemia compared to standard drug. Concurrent histological studies of the pancreas of these animals showed comparable regeneration by alcoholic and aqueous extracts which were earlier, necrosed by alloxan. The data suggests that the alcoholic extracts (200 mg/kg) may be effectively utilized as antidiabetic and antihyperlipidemic agents and supports its traditional usage in the control of diabetes. However, further pharmacological evaluations are required to isolate and identify the active antidiabetic and antihyperlipidemic principles in the plant as well as elucidating their mechanisms of action.